Exercise intervention to reduce mobile phone addiction in adolescents: a systematic review and meta-analysis of randomized controlled trials - Li, Zuxian; Xia, Xue; Sun, Qilong; Li, Yansong (Frontiers in Psychology, 2023)
Background: The growing problem of adolescent mobile phone addiction has attracted significant attention, underscoring the importance of identifying approaches to address it. Exercise has been found to reduce adolescent mobile phone addiction; however, its mechanism remains unclear. This review aims to elucidate the potential moderating factors between exercise and mobile phone addiction based on previous studies to provide a reference for adolescents to effectively participate in exercise to reduce mobile phone addiction. Methods: Articles were searched in the CNKI, Web of Science, Scopus, Cochrane, PsycINFO, and PubMed databases according to the inclusion criteria and followed the Preferred Reporting Items for Systematic Assessment and Meta-analysis (PRISMA). The quality of the literature was assessed by two independent reviewers using the Cochrane Collaboration Risk of Bias tool for methodological quality assessment. Meta-analysis was performed using Stata 15.1 software for Meta-analysis, standardized mean difference (SMD) was combined using a random effects model, and subgroup analysis was used to explore heterogeneity. Results: A total of 12 studies, 17 samples, and 861 subjects were included in the meta-analysis, and all studies were randomized controlled trials. The findings revealed that the exercise intervention significantly reduced mobile phone addiction in adolescents (SMD = –3.11; 95% CI: –3.91, –2.30; P<0.001). The intervention effect was moderated by multiple variables, such as the measurement tools, exercise intervention types, cycles, frequency, and duration of a single exercise intervention. Conclusions: Our findings suggest that exercise could serve as an effective strategy for preventing or ameliorating mobile phone addiction in adolescents. Based on the results of this study, we encourage mobile phone-addicted adolescents to engage in a single exercise using a mix of skills for 30–60 min three or more times weekly for more than eight consecutive weeks.